The Ratio of Oxygen Uptake From Ventilatory Anaerobic Threshold to Respiratory Compensation Point Is Maintained During Incremental Exercise in Older Adults - Kominami, Kazuyuki; Imahashi, Keiko; Katsuragawa, Toko; Murakami, Mitsuyo; Akino, Masatoshi (Frontiers in Physiology, 2022)
Introduction The period from ventilatory anaerobic threshold (VAT) to respiratory compensation point (RCP) during incremental exercise (isocapnic buffering phase) has been associated with exercise tolerance and skeletal muscle composition. However, several reports compare younger and older healthy adults, and specific age-related changes are unclear. This study aimed to examine the oxygen uptake (VO2) from VAT to RCP and its change over time in younger and older healthy adults. Methods A total of 126 consecutive participants were divided into two groups (95 younger and 31 older than 50 years of age) who underwent cardiopulmonary exercise testing, and VAT and RCP were determined. The ratio (RCP/VAT) and difference (ΔVO2 RCP-VAT) were calculated from the VO2 of VAT and RCP and compared between groups and ages. Statistical analyses included t-tests and Spearman’s correlation tests, and the significance level was set at <5%. Results RCP/VAT was not significantly different (1.40 ± 0.19 vs. 1.59 ± 0.24, p = 0.057) but weakly correlated with age (r = −0.229, p = 0.013, y = −0.0031x + 1.7588, lowering rate: 0.185%/year). Conversely, ΔVO2 RCP-VAT was significantly lower in the older group (7.7 ± 3.1 vs. 13.8 ± 4.9 ml/kg/min, p < 0.001) and correlated significantly with age (r = −0.499; p < 0.001; y = −0.1303x + 16.855; lowering rate, 0.914%/year). Conclusion ΔVO2 RCP-VAT was considered to be a poor indicator of lactate buffering capacity in the IB phase because both VAT and RCP were greatly affected by age-related decline. Conversely, RCP/VAT was suggested to be an index not easily affected by aging.